KADAR SGPT (Serum Glutamic Pyruvat Transminase) PADA AKSEPTOR KONTRASEPSI PIL KB - atun farihatun; Erni Siti Nur Janah; Dewi Kania Yulianti; Edhiatmi Edhiatmi; Dewi Yayuningsih (LPPM STIKes Muhammadiyah Ciamis, 2020)
SGPT (Serum Glutamic Pyruvat Transminase) enzymes are found in liver, heart, muscle and kidney tissue. SGPT has a relatively high specificity for liver damage. Long-term use of birth control pills can cause liver tissue damage. Impaired liver function occurs due to the presence of the hormone progesterone which causes the flow of bile to slow down, and if it lasts a long time, the bile ducts become blocked, so the bile in the blood increases. The purpose of this study was to determine the level of SGPT in the acceptors of contraceptive pills in Ciamis Regency. This research method is a descriptive study. Based on the results of the examination of SGPT levels carried out on 30 family planning pill acceptors in the Ciamis Regency, it was found that 9 people (30%) had high ALT levels and the results were 21 people (70%) had normal SGPT levels.